PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJARIPAPADA SISWA KELAS VII SMP NEGERI 2 BATU HAMPAR TAHUN PELAJARAN 2015/2016 - Maryani, Levi; Sayuti, Irda; Syafii, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study was conducted to determine the students learning outcome of science by directly applying the learning model. This research was done in class VII SMP Negeri 2 Batu Hampar March to April 2016 the academic year 2015/2016. This research is a classroom action research conducted in two cycles of planning, implementation, observation and reflection. The data collected in this study is the result of learning students consisting of absorption, mastery learning, student activities and teacher's activities. Data were collected using tests and observation sheet. The results showed that the student’s learning outcomes comprise absorption in the first cycle is 78.75% (enough) increased in the second cycle is 81.73% (good), mastery of students in the first cycle that 87.50% (complete category) increased in the second cycle of 100% (category complete), the activity of students in the first cycle is 87.88% (good) increased in the second cycle is 90.63% (excellent), the activities of teachers in the first cycle is 87.50%, ( good) increased in the second cycle of 100% (excellent). It can be concluded that the application of direct learning model can improve learning outcomes IPA class VII SMP Negeri 2 Batu Hampar the academic year 2015/2016.Keywords: Direct Learning, Learning outcomes